Analisis Strategi Pemasaran untuk Meningkatkan Penjualan UMKM Ayam Geprek Melotot di Kota Jambi - Putri Andini; Ahmad Syahrizal; Neneng Sudharyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Melotot Geprek Chicken Shop which is located at Jl. Sk Syahbudin, Ruko Puri Mayang, Mayang Mangurai, Jambi city. This Geprek Chicken Shop not only provides Geprek Chicken, but also provides toppings such as omelettes, liver gizzards, quail eggs, tofu-tempeh, perkedel, fried petai and others. The phenomenon or event that can be felt directly by researchers is, the Geprek Melotot Chicken Shop with a simple and not luxurious building design, ordinary service, and product sales that only use a word of mouth strategy, resulting in a lack of turnover as expected and what has been achieved. planned. So the aim of this research is to find out what marketing strategies are to increase sales, what obstacles are faced and what are the solutions in dealing with marketing strategies. The discussion of this research is related to the theory of increasing sales, MSMEs, Marketing Strategy, Halal Labeling, and Constraints in MSME Development. This research is a type of Qualitative research with a descriptive approach, using primary data sources and secondary data. The subjects of the research are Shop Owners and Consumers. Data collection techniques are observation, interviews and documentation. The results of this study indicate that the strategy implemented by Toko Ayam Geprek Melotot in increasing sales is by using the 9P marketing mix strategy (product, price, place, promotion, people, process, physical evidence, payment, packaging), namely product strategy, price, location, promotion, people, process, physical evidence, payment, and packaging.